Aspartate β-hydroxylase as a target for cancer therapy - Kanwal, Madiha; Smahel, Michal; Olsen, Mark; Smahelova, Jana; Tachezy, Ruth (Journal of experimental & clinical cancer research, 2020)
As metastasis is a major cause of death in cancer patients, new anti-metastatic strategies are needed to improve cancer therapy outcomes. Numerous pathways have been shown to contribute to migration and invasion of malignant tumors. Aspartate β-hydroxylase (ASPH) is a key player in the malignant transformation of solid tumors by enhancing cell proliferation, migration, and invasion. ASPH also promotes tumor growth by stimulation of angiogenesis and immunosuppression. These effects are mainly achieved via the activation of Notch and SRC signaling pathways. ASPH expression is upregulated by growth factors and hypoxia in different human tumors and its inactivation may have broad clinical impact. Therefore, small molecule inhibitors of ASPH enzymatic activity have been developed and their anti-metastatic effect confirmed in preclinical mouse models. ASPH can also be targeted by monoclonal antibodies and has also been used as a tumor-associated antigen to induce both cluster of differentiation (CD) 8+ and CD4+ T cells in mice. The PAN-301-1 vaccine against ASPH has already been tested in a phase 1 clinical trial in patients with prostate cancer. In summary, ASPH is a promising target for anti-tumor and anti-metastatic therapy based on inactivation of catalytic activity and/or immunotherapy.
Keywords: nádory plic; Membrane Proteins; Lung Neoplasms; Humans; Metastasis; Mixed Function Oxygenases; Molecular Targeted Therapy; Calcium-Binding Proteins; Antineoplastic Agents; ASPH; Muscle Proteins; lidé; Immunotherapy; oxygenasy se smíšenou funkcí; svalové proteiny; Small molecule inhibitor; prognóza; proteiny vázající vápník; cílená molekulární terapie; protinádorové látky; membránové proteiny; Prognosis